Structure and function of membrane proteins : proceedings of the International Symposium on Structure and Function of Membrane Proteins held in Selva di Fasano (Italy), May 23-26, 1983 - Quagliariello, E. (Ernesto); Palmieri, F. (Ferdinando) (Developments in bioenergetics and biomembranes, 1983)
Structure and Function of Membrane Proteins documents the proceedings of the International Symposium on Structure and Function of Membrane Proteins held in Selva di Fasano on May 23-26, 1983.